How Microeconomic Drivers and Macroeconomic Forces Shape Firm Value in State Owned Enterprise Groups Listed on the Indonesia Stock Exchange (2022–2024) - Ika Mutiara Khadijah; Tony Sudirgo (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2026)
This study examines how intellectual capital, firm characteristics, good corporate governance (GCG), dividend policy, inflation, and exchange rates affect the firm value of BUMN Group companies listed on the Indonesia Stock Exchange during 2022–2024. The research uses 51 observations over three years, relying on secondary data from financial statements, annual reports, and macroeconomic sources. Firm value is measured using Tobin’s Q, while the independent variables consist of GCG indicators (independent commissioners, audit committee, managerial ownership), intellectual capital measures (VACA, STVA, VAIC), firm characteristics (asset growth, size, leverage, ROE, current ratio), dividend payout ratio, and macroeconomic variables (inflation and exchange rates). Data analysis employs multiple linear regression using SPSS 26. The results show that only independent commissioners and current ratio significantly influence firm value, whereas all other variables do not have a significant effect on the firm value of BUMN Group companies.